Catatan Penilaian Ketercapaian Perguruan Tinggi dalam Menerapkan Pembelajaran Jarak Jauh (E-Learning) di Universitas Pamulang, Universitas Terbuka, dan Universitas Bina Nusantara - Mawardi Nurullah (Faculty of training and education, Pamulang university, 2022)
The research conducted by the researcher aims to find information regarding the readiness of students in distance learning using the e-learning lecture model, the process of implementing e-learning learning in teaching and learning activities, the inhibiting factors for using online lectures. Thus, the results of the study showed that students were ready to accept the online learning process and their readiness in the application of ICT, however, several obstacles were found in the distance lecture process, such as the internet signal network that was not supported and adequate so that the process of implementing online lectures was not optimal.It was found that the aspects that became obstacles in distance learning using e-learning, which found 3 factors in it, namely: the lack of knowledge dissemination about e-learning lectures was less intense, there was still at least the use of tools and features provided in the e-learning model and still found